Isolation of a methane-oxydizing bacterium for the study on single cell protein production from methane - Thu, Nguyễn Thị Hiếu; Hằng, Đinh Thuý (Vietnam Journal of Biotechnology, 2016)
Single cell protein (SCP) can be produced from biomass of different types of microorganisms that have high protein content such as yeast, filamentous fungi, algae and bacteria. In comparison to animal and plant protein sources, this kind of protein has several advantages, namely high protein and nutrient contents, being produced in fermenters with the use of variety of organic wastes, independence in agriculture land or climate conditions. Methane oxidizing bacteria (MOB) are considered as good candidates for SCP production and have been intensively studied recently. In the present study, a MOB strain BG3 was isolated from wastewater of an anaerobic digester via enrichment and isolation procedures using methane as the only carbon and energy sources. Strain BG3 comprised of oval-shaped cells of 0,8-1´16 -1,8 μm in size, almost nonmotile. Based on comparative analyses of the 16S rDNA partial sequences, strain BG3 was identified as a member of the Methylomonas genus, the most closely related species was Methylomonas koyamae (97% homology). This was also confirmed by analyses of sequence of the pmoA gene, encoding for a-subunit in the methane-monooxygenase in the strain. Besides methane, strain BG3 also utilized methanol for the growth. It has been shown that methane-fed culture of strain BG3 could produce 68.69 g crude protein per 100 g CDW and the according methane to biomass conversion efficiency was 2,8 m3 methane×kg-1 dry biomassas. Owing the capability of utilization of methane, the second important greenhouse gas, for the production of protein source for animal feed, strain BG3 would have a great application potential in Vietnam. Strain BG3 was designated as Methylomonas sp. BG3 and its 16S rDNA and pmoA gene sequences were deposited at the GenBank with accession numbers of KJ081955 and KJ081956, respectively.